(3Md Tchc cJGH CbdjOS aj GdCUhd hTQM eYGfjgs - (3GdMSf Hf GdMSf Hf GdgjKe GdeUQjs; (3GbdjOSs
(3ChdgG (B:s
(3GdMeO ddg hMOg cd eYfi JZeV MbjbJg hJNai HGdHOjgI NhGUg hjTGHg ai HYV CMhGdg s
(3BNQgG (B:s
(3hgPG Mjf fNJe cJGHfG gPG hfTcQ Gddg JYGdi Ydi fYeg s
(3GdJhKjbGJ GdeQLYjI (B:s
(3HQhcdeGf (B- (3GdLRA (B1 - (3U (B469 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA QjGVjGJ (B- (3bSe (B3 - (3U (B42 s
(3eUOQ GbJfGA GdCUd (B:s
(3ecJHI LGeYI GSJGfHhd (B(800) s
Keywords: (3GdQjGVjGJs